Ein CrossMapping Partenheimer in China, Peking Beijing Nanking Nanjing. - China National Museum of Fine Arts, Beijing; Nanking Museum, Nanking; Bonnet, Anne-Marie; Clement, Wolfgang; Gaissmayer, Michel; Goepper, Roger; von Graevenitz, Antje; Grünbein, Durs; Guoping, Zhou; Huping, Xu; Jianguo, Li; Kluge, Alexander; et al. (Düsseldorf : Richter Verlag Düsseldorf, 2001)
At the beginning of the year 2000, and for the first time ever, a comprehensive exhibition of the works of a contemporary German artist was mounted in China's two most important museums : The China National Museum of Fine Arts in Beijing and the Nanjing Museum. It met with an extraordinary response from both the Chinese and the German media. This publication documents not only the exhibitions in China and the installation of the sculpture World Axis in the outer precinct of the Forbidden City in Beijing and on a boat on the Yangtze-River near Chenchiang but also the results of the dialogue between Chinese and German artists, philosophers, writers, architects, art historians and Sinologists. The different aesthetic perceptions of Oriental and European traditions have just as important a part to play in CrossMapping as the treatment of contemporary cultural and social tendencies. The fact that Partenheimer's abstract art served the Chinese philosophers Sun Zhouxing and Zhou Guoping as a starting point for a discussion on issues of contemporary art underlines the significance of the project. Among the German writers in this book are, besides art historians and theorists, the poet Durs Grünbein and the author and film-maker Alexander Kluge. Their contributions reveal their respective approaches towards contemporary art. Jürgen Partenheimer counts among the internationality most renowned German artists of his generation. His art is marked by a minimalist abstraction, which opens up an inversely wide spectrum of associations. These creative processes represent a model for an interpretation of the world and reality, which develop new standards of perception, run counter to all popular trends and combine his art with serious theoretical discourse.
bibliog. p. 236-244
biog. p. 232
Duits
Engels
Jurgen Partenheimer : CrossMapping Partenheimer in China, Peking Beijing Nanking Nanjing, China National Museum of Fine Arts, Beijing, 15. Januar bis 30. Januar 2000 / Nanking Museum, Nanking, 29. Februar bis 20. März 2000 / Symposium, Kunstmuseum Bonn, 5. und 6. März 2001
boek
Keywords: Partenheimer, Jürgen; China